Machiavellian Leadership Communication in Korean Manhwa - Taufiq, Muhammad (Communicare : Journal of Communication Studies, 2025)
This study examines the representation of Machiavellian leadership communication in the Korean manhwa Heavenly Demon Can’t Live a Normal Life. Departing from conventional studies that locate Machiavellianism within formal political institutions or historical leadership, this research positions popular visual narratives as significant sites for the construction and dissemination of power discourse. Using a qualitative approach and critical discourse analysis, the study analyses narrative structures, character dialogues, and visual symbolism to uncover how leadership, legitimacy, and organizational control are communicatively produced. The findings reveal that leadership in the manhwa is constructed as a strategic communicative practice rather than mere coercion or inherited authority. The protagonist, Roman Dmitri, establishes legitimacy through a combination of performative competence, centralized decision-making, symbolic violence, and strategic displays of care. These communicative practices generate voluntary consent and organizational loyalty, aligning closely with Machiavellian principles that emphasize effectiveness, stability, and the management of perception. Furthermore, the manhwa integrates political communication and organizational communication by depicting power as a continuous process of discourse reproduction within a hierarchical structure. Authority is normalized through narratives that frame domination as necessary, rational, and morally justified when accompanied by protection and responsibility. This study contributes to communication scholarship by demonstrating that Korean manhwa functions as a meaningful political-organizational text, capable of articulating complex Machiavellian leadership logics through visual storytelling.